Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To solve the equation \(x^2 - 12x + 36 - 90 = 0\), let's follow a systematic approach:
1. Simplify the given equation:
[tex]\[ x^2 - 12x + 36 - 90 = 0 \][/tex]
Combine the constant terms:
[tex]\[ x^2 - 12x - 54 = 0 \][/tex]
2. Identify the coefficients for the quadratic equation \(ax^2 + bx + c = 0\):
Here, \(a = 1\), \(b = -12\), and \(c = -54\).
3. Calculate the discriminant:
The discriminant \(D\) is given by the formula:
[tex]\[ D = b^2 - 4ac \][/tex]
Plugging in the coefficients:
[tex]\[ D = (-12)^2 - 4(1)(-54) \][/tex]
Simplify the expression:
[tex]\[ D = 144 + 216 = 360 \][/tex]
4. Find the roots using the quadratic formula:
The quadratic formula is:
[tex]\[ x = \frac{-b \pm \sqrt{D}}{2a} \][/tex]
Substitute the values of \(a\), \(b\), and \(D\):
[tex]\[ x = \frac{12 \pm \sqrt{360}}{2} \][/tex]
Simplify \(\sqrt{360}\):
[tex]\[ \sqrt{360} = \sqrt{36 \times 10} = 6\sqrt{10} \][/tex]
Substitute back into the formula:
[tex]\[ x = \frac{12 \pm 6\sqrt{10}}{2} \][/tex]
Simplify the expression:
[tex]\[ x = 6 \pm 3\sqrt{10} \][/tex]
Thus, the solutions to the equation \(x^2 - 12x - 54 = 0\) are
[tex]\[ x = 6 + 3\sqrt{10} \quad \text{and} \quad x = 6 - 3\sqrt{10} \][/tex]
Comparing these solutions to the given choices:
\( \boxed{1} \): \( x = 6 \pm 3\sqrt{10} \)
\(2\): \( x = 6 \pm 2\sqrt{7} \)
\(3\): \( x = 12 \pm 3\sqrt{22} \)
\(4\): \( x = 12 \pm 3\sqrt{10} \)
The correct solution corresponds to choice [tex]\(\boxed{1}\)[/tex]: [tex]\( x = 6 \pm 3\sqrt{10} \)[/tex].
1. Simplify the given equation:
[tex]\[ x^2 - 12x + 36 - 90 = 0 \][/tex]
Combine the constant terms:
[tex]\[ x^2 - 12x - 54 = 0 \][/tex]
2. Identify the coefficients for the quadratic equation \(ax^2 + bx + c = 0\):
Here, \(a = 1\), \(b = -12\), and \(c = -54\).
3. Calculate the discriminant:
The discriminant \(D\) is given by the formula:
[tex]\[ D = b^2 - 4ac \][/tex]
Plugging in the coefficients:
[tex]\[ D = (-12)^2 - 4(1)(-54) \][/tex]
Simplify the expression:
[tex]\[ D = 144 + 216 = 360 \][/tex]
4. Find the roots using the quadratic formula:
The quadratic formula is:
[tex]\[ x = \frac{-b \pm \sqrt{D}}{2a} \][/tex]
Substitute the values of \(a\), \(b\), and \(D\):
[tex]\[ x = \frac{12 \pm \sqrt{360}}{2} \][/tex]
Simplify \(\sqrt{360}\):
[tex]\[ \sqrt{360} = \sqrt{36 \times 10} = 6\sqrt{10} \][/tex]
Substitute back into the formula:
[tex]\[ x = \frac{12 \pm 6\sqrt{10}}{2} \][/tex]
Simplify the expression:
[tex]\[ x = 6 \pm 3\sqrt{10} \][/tex]
Thus, the solutions to the equation \(x^2 - 12x - 54 = 0\) are
[tex]\[ x = 6 + 3\sqrt{10} \quad \text{and} \quad x = 6 - 3\sqrt{10} \][/tex]
Comparing these solutions to the given choices:
\( \boxed{1} \): \( x = 6 \pm 3\sqrt{10} \)
\(2\): \( x = 6 \pm 2\sqrt{7} \)
\(3\): \( x = 12 \pm 3\sqrt{22} \)
\(4\): \( x = 12 \pm 3\sqrt{10} \)
The correct solution corresponds to choice [tex]\(\boxed{1}\)[/tex]: [tex]\( x = 6 \pm 3\sqrt{10} \)[/tex].
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.